ALIH TEKNOLOGI PEMBUATAN ALAT PENETAS TELUR SEDERHANA DI DESA ORO-ORO BULU PASURUAN - Mauliana, Metatia Intan; Hasanah, Fitria Nur; Azizah, Nuril Lutvi (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. Indonesia is one of the countries with the most consumption of processed chicken in Asia. This causes businesses and UKM in the field of chicken farming to be quite attractive. Oro-oro Bulu village is one of the villages located in the Rembang district. This village with the area and population density have the potential of developing chicken farming business. Chicken farms in the village of Oro Bulu although still relatively small but quite promising. It's just that chicken farmers in this village are still unable to produce their chicken seeds. Chicken seeds are usually imported by farmers from the Mojosari and Kediri regions. This is due to a lack of understanding of breeders on nurseries and lack of knowledge and maintenance of the hatchery equipment needed.Therefore, the researchers took the initiative to socialize understanding of chicken breeding and develop a simple egg incubator to help Oro Bulu farmers to produce chickens / DOC independently. The methods of implementation in IbM activities include using methods with counseling to deliver material that is theoretical and motivational, demonstration of assembling simple egg incubators directly. The entire socialization process is carried out by the implementing team of activities involving lecturers and students with areas of expertise that are by the needs of the field. Based on the results of respondents' questionnaire data processing, it was obtained that the average 71.8% stated that there was an increase in motivation and 77.5% stated the success of technology transfer by respondents after participating in the socialization activities. So that it can be said that this IbM activity has been successfully implemented. Abstrak. Indonesa merupakam salah satu Negara dengan pengkonsumsi olahan ayam terbanyak di Asia. Hal ini menyebabkan bisnis dan UKM bidang peternakan ayam cukup diminati. Desa Oro-oro bulu merupakan salah satu desa yang terletak di kecamatan Rembang. Desa dengan Luas dan kepadatan penduduk ini memiliki potensi usaha peternakan ayam yang sedang berkembang. Peternakan ayam di desa Oro bulu meskipun masih terbilang kecil namun cukup menjanjikan. Hanya saja peternak ayam di desa ini masih belum mampu menghasilkan bibit ayam sendiri. Bibit ayam biasanya didatangkan oleh peternak dari wilayah Mojosari dan Kediri. Hal ini dikarenakan kurangnya pemahaman peternak akan pembibitan dan minimnya pengetahuan dalam penggunaan dan perawatan peralatan penetasan telur yang dibutuhkan. Oleh karena itu, peneliti berinisiatif untuk melakukan sosialisasi pemahaman mengenai pembibitan ayam dan mengembangkan alat penetas telur sederhana untuk membantu peternak desa Oro bulu dalam menghasilkan bibit ayam/DOC secara mandiri. Metode pelaksanaan pada kegiatan IbM antara lain menggunakan metode dengan penyuluhan untuk penyampaian materi yang bersifat teori dan motivasi, demonstrasi perakitan alat penetas telur sederhana secara langsung. Keseluruhan proses sosialisasi dilaksanakan oleh tim pelaksana kegiatan yang melibatkan dosen dan mahasiswa dengan bidang keahlian yang sesuai dengan kebutuhan lapangan. Berdasarkan hasil pengolahan data angket responden diperoleh sebanyak rerata 71.8% menyatakan adanya kenaikan motivasi dan 77.5% menyatakan keberhasilan alih teknologi oleh responden setelah mengikuti kegiatan sosialisasi. Sehingga dapat dikatakan bahwa kegiatan IbM ini telah berhasil dilaksanakan.